Analysis of The Effect of Rooftop PV Integration on The Reliability of Medium Voltage Power Distribution Network - Jannah, Miftahul; Nasution, Muhammad Fadli; Hudaya, Chairul (International Journal of Electrical, Energy and Power System Engineering, 2026)
The service area of PLN UP3 Cikupa possesses significant potential for the utilization of rooftop photovoltaic (PV) systems, particularly in the industrial sector, which generally has large roof areas and high energy consumption. This study aims to analyze the impact of rooftop PV integration on the reliability of the medium-voltage distribution system in the Stanley feeder. The evaluation was conducted through simulations using ETAP software under two load conditions: peak load and no-load, with PV penetration levels ranging from 0% to 100%. The results indicate that up to 100% PV penetration (4 MW), no voltage violations occurred at the CKP92 substation. However, there was a significant decline in the power factor, dropping to 7% under peak load conditions and to -100% under no-load conditions starting at 20% penetration, indicating reverse power flow. The PV penetration was further increased beyond 100%, and it was found that the maximum PV penetration without violating voltage limits was 400% (16 MW). At 400% penetration, overvoltage occurred on several buses, and overload was observed on specific cables, with the three-phase short-circuit current approaching the system protection threshold (15.977 kA out of a 16 kA limit). Nonetheless, rooftop PV integration provided benefits such as improved voltage profiles and enhanced system reliability, as indicated by reductions in SAIDI, SAIFI, and EENS indices. These findings suggest that rooftop PV can be optimally integrated up to a certain limit without compromising distribution system performance.